Clinical characteristics and outcomes in super‐elderly patients (>85 years) with heart failure: single center observational study in Japan. Issue 2 (5th March 2014) - Fujii, Noriyuki; Naito, Kazuyuki; Nakahara, Norifumi; Nakano, Atsushi; Takagi, Satoru
<x xml:space="preserve">Abstract</x> Aim The number of elderly patients with heart failure is increasing in Japan owing to the increase in the aging population. In the field of emergency medicine, the treatment and management of elderly patients with heart failure are key issues. We aimed to clarify the clinical characteristics and outcomes of these patients. Methods We enrolled 72 consecutive patients (age, 76.5 ± 12.5 years) with heart failure who were admitted to our hospital between January 1 and December 31, 2010. The characteristics and outcomes of super‐elderly patients aged >85 years (n = 21) were compared with those of patients aged ≤85 years (n = 51). Results The overall prevalence of chronic atrial fibrillation was high (43.1%). Underlying diseases, left ventricular function, renal function, in‐hospital mortality, hospital stay period, and major complications were similar between the two groups. The super‐elderly group had a significantly higher mortality rate and lower event‐free survival rate after discharge (log–rank test, P = 0.0018 and P = 0.0032, respectively). The incidence of readmission for heart failure recurrence was 55.0% in the super‐elderly group and 25.0% in the younger group. Conclusion There were no significant differences in the background characteristics and in‐hospital treatment between super‐elderly heart failure patients and younger patients. High mortality and cardiovascular event rates after discharge were observed in the super‐elderly group.